Whole eye axial biometry during accommodation using ultra-long scan depth optical coherence tomography - Zhong, Jianguang (2014)
PURPOSE: To investigate changes of whole eye axial biometry during accommodation using ultra-long scan depth optical coherence tomography (UL-OCT). DESIGN: Prospective, observational case series. METHODS: Twenty-one adult subjects were enrolled. Using UL-OCT, the left eye of each subject was imaged with relaxed (0 D) and accommodative stimuli (+6 D). Full eye biometry included central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness, vitreous length and axial length (AL). RESULTS: During accommodation (+6 D), the axial biometry of the whole eye changed significantly. Compared to the rest state, ACD at the accommodative state decreased significantly from 3.128 ± 0.305 mm to 2.961 ± 0.298 mm (paired t-test, P < 0.001). The lens thickness increased significantly from 3.723 ± 0.237 mm to 3.963 ± 0.234 mm (P < 0.001). The vitreous length decreased significantly from 17.129 ± 0.864 mm to 17.057± 0.848 mm (P < 0.001). AL was 24.519 ± 0.917 mm at the rest state and increased to 24.545±0.915 mm with +6 D accommodation stimulus. The elongated AL of 26.1 ± 13.4 μm between the rest and accommodative states was significant (P < 0.001). CONCLUSIONS: During accommodation, whole eye axial biometry changed, including a decrease in ACD and vitreous length, and an increase in lens thickness and AL. UL-OCT provides an alternative method that is suitable for full eye biometry during accommodation.